Contact Lens–Related Complications in Nursing Practice: Risk Assessment, Patient Education, and Prevention of Ocular Morbidity - Al Omar, Nada Abdalaziz; Njoud Saeed Mohammed Alasmari; Hazam Shari Alharthy; Namah Abdullah Hussein Alshokhah; Jawaher Owaid Alrwailiy; Khaznah Hadi Alharbi; Munayfah Oudah Aldhafeeri; Yesmin Mansour Aid Al-Azmi; Mubarakah Saeed Mohammed Alabsi; Amnah Ahmed Hussain Khudashi; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Contact lens (CL) use has grown globally, offering cosmetic and therapeutic benefits but introducing risks of ocular complications due to hypoxia, microbial contamination, and tear film disruption. These complications range from mild irritation to vision-threatening infections such as microbial keratitis. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review contact lens–related complications, their pathophysiology, and the role of nursing in prevention, early detection, and patient education. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature-based analysis was conducted, synthesizing evidence on CL-induced corneal and conjunctival disorders, functional tear–lens interactions, and clinical management strategies. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> CL wear alters ocular physiology, reducing oxygen transmission and destabilizing tear film, which predisposes epithelial edema, microcysts, abrasions, and inflammatory conditions. Infectious keratitis, particularly due to <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Pseudomonas aeruginosa<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> and <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Acanthamoeba<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">, remains the most severe complication, often linked to poor hygiene and water exposure. Conjunctival disorders such as allergic conjunctivitis and giant papillary conjunctivitis further compromise lens tolerance. Preventive strategies include patient education on hygiene, avoidance of overnight wear, and prompt discontinuation upon symptom onset. Nursing interventions—structured counseling, triage, and monitoring—are pivotal in reducing morbidity. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> CL-related complications are largely preventable through adherence to hygiene protocols, individualized lens selection, and multidisciplinary care. Nurses play a critical role in patient education and early recognition of warning signs, thereby minimizing irreversible ocular damage.